What are management systems? The effect of management style according to system dynamics (2017)
Organizational management models involve various perspectives, such as management style, cultural dimensions, business models, organizational models, behavioural models and organizational learning. Each of these perspectives has an effect and thus a bearing on management. Accordingly, it becomes difficult to determine which of these perspectives is the most significant for a management model. For example, management style can be held to be a variable with a major impact on the organization because it affects the definition of organizational objectives while coordinating and controlling resources. Therefore, this study presents a proposal for the characterization of management models and presents in the form of a causal chart what could be considered a matrix framework for an organizational management model. To construct this matrix, possible relationships were established between each of the previously proposed systems considered to constitute organizations.